Beragam Cara, Satu Tujuan: Implementasi Pembelajaran Berdiferensiasi pada Materi Perakitan Produk di SMK Negeri 2 Kabupaten Tangerang - Ade Ferdiansyah (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This study aims to increase student learning participation in creative product and entrepreneurship lessons for product assembly materials at SMK Negeri 2 Tangerang Regency using differentiated learning strategies. This type of research is a case study research. The subjects of this study are grade XII students of TITL 1 SMK Negeri 2 Tangerang Regency in the odd semester of the 2024/2025 school year totaling 51 people. The data collection instruments in this study are class observation and questionnaires. The research method uses a qualitative approach. This research was carried out in three meetings for learning activities, including the provision of treatment according to the learning style of each group. The results of the study show that by using differentiated learning strategies, the level of student learning participation increases. This can be seen from the level of enthusiasm of students in receiving learning. Thus, the researcher concluded that using differentiated learning strategies can increase student learning participation in creative product and entrepreneurship lessons, product assembly materials for grade XII TITL 1 SMK Negeri 2 Tangerang Regency. Therefore, teachers should use learning strategies that are in accordance with the learning needs of students to achieve the learning goals that have been determined. With the implementation of the right learning strategy, students are able to accommodate their learning needs.